Studies on floral morphology and biology in Jasminum spp. - KALAIYARASI, A; DHANANJAYA, M V; NAIR, SUJATHA A; KUMAR, RAJIV; YOGEESHA, H S; MUNIKRISHNAPPA, P M; DEVAPPA, V; PAVITHRA, S (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out to study the floral morphology and biology of 5 genotypes during 2016-17. Many flowered cymes both terminal and axillary were observed in J. auriculatum and J. grandiflorum; whereas, cluster bearing flowers in terminal position were observed in J. multiflorum (IIHR JM–1 and IIHR JM–2), J. calophyllum, J. flexile and J. malabaricum. Flower bud was pointed and long in all genotypes; its colour was either green white (157 B) or white (155 C) or white (155 D).Tinge on flower bud was observed in J. grandiflorum (CO.1 Pitchi and Arka Surabhi), J. rigidum, J. nitidum and J. malabaricum. Flower petal tip was either sharp or blunt and flower colour on opening was either white (155 C) or white (155 D) or white with pinkish underneath (155 D) in all the genotypes. Among the 15 genotypes, J. grandiflorum var. CO.1 Pitchi recorded longest flower bud length (4.81 cm) and corolla tube length (2.92 cm); however, maximum corolla length was recorded in J. nitidum (2.15 cm). Maximum number of forks per cymes was recorded in J. auriculatum var. CO.1 Mullai (40.13). Maximum number (6.51) and length of calyx lobe (1.28 cm) was recorded in J. multiflorum –IIHRJM-2 and J. nitidum, respectively. Flower diameter ranged from 1.74 (J. auriculatum-IIHRJA-2) to 4.93 cm (J. nitidum), whereas number of petals varied from 4.97 (J. grandiflorum var. CO.1 Pitchi) to 10.67 (J. nitidum). All genotypes recorded one style per pistil and its length varied from 0.42 cm (J. auriculatum var. CO.2 Mullai) to 2.32 cm (J. grandiflorum var. CO.1 Pitchi). Anthesis and anther dehiscence was recorded earlier in summer months, while, it was delayed during cooler months. However, the peak anthesis was observed from 6:00 to 7:00 p.m. and anther dehiscence from 4:00 to 7:00 p.m. The earliest anthesis was observed in J. auriculatum genotypes and anther dehiscence was observed in J. auriculatum and J. multiflorum genotypes. The stigma was receptive 12 h before an thesis and up to 24 h of anthesis. The maximum receptivity was observed from the time of anthesis to 12 h after anthesis.